2022
DOI: 10.1111/jfpp.16346
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity and rheological, textural properties of ice cream produced from camel's milk with blueberry

Abstract: In recent years, camel milk has become attractive due to its therapeutic properties, and is more preferred by consumers (Abdulqadir, 2019). It is one of the main components for human nutrition in many places of the world. It contains all nutritional elements like cow milk, and it is beneficial for human nutrition. Camel's milk is frothy when shaken slightly.Its odor is like regular milk, and it is tasty and sharp. Depending on the drinking water and forage used, sometimes the flavor of camel's milk can be slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
(105 reference statements)
2
10
2
Order By: Relevance
“…Redness ( a *) and yellowness ( b *) values of the ice cream samples increased by addition of rowanberry pulp and probiotic. Previous studies (Hwang et al ., 2009; Karaman et al ., 2014; Öztürk et al ., 2018; Sayar et al ., 2022), which they declared that the use of fruit in ice cream production decreased the brightness value of ice cream, were in agreement with our study. In addition, (Goktas et al ., 2022) and (Öztürk et al ., 2018) stated that using probiotics in ice cream production raised the brightness value.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Redness ( a *) and yellowness ( b *) values of the ice cream samples increased by addition of rowanberry pulp and probiotic. Previous studies (Hwang et al ., 2009; Karaman et al ., 2014; Öztürk et al ., 2018; Sayar et al ., 2022), which they declared that the use of fruit in ice cream production decreased the brightness value of ice cream, were in agreement with our study. In addition, (Goktas et al ., 2022) and (Öztürk et al ., 2018) stated that using probiotics in ice cream production raised the brightness value.…”
Section: Resultssupporting
confidence: 93%
“…Statistical differences between the samples were found only for D6, D8 and D10 ( P ≤ 0.05) and using rowanberry pulp at different ratio did not affect the TDM results of the ice cream products. (Karaman et al ., 2014) and (Sayar et al ., 2022) reported that increasing fruit concentration decreased the TDM value of ice cream. However, (Öztürk et al ., 2018) reported that TDM values of probiotic ice cream samples containing white and blue myrtle fruit at 12% ratio were not different from control sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations